1995
DOI: 10.1016/0026-0495(95)90296-1
|View full text |Cite
|
Sign up to set email alerts
|

The associations of high-density lipoprotein subclasses with insulin and glucose levels, physical activity, resting heart rate, and regional adiposity in men with coronary artery disease: The stanford coronary risk intervention project baseline survey

Abstract: We used nondenaturing polyacrylamide gradient gel electrophoresis to examine the associations of high-density lipoprotein (HDL) subclasses with adiposity, physical activity, resting heart rate (an indicator of sympathetic drive), and plasma insulin and glucose levels in 97 men with angiographically documented coronary artery disease. These men neither smoked nor used medications known to affect lipoproteins. The absorbency of protein stain was used as an index of mass concentrations at intervals of 0.01 nm wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 63 publications
5
22
0
Order By: Relevance
“…Consistent with previous studies, we found that the distribution of HDL sizes was significantly shifted from large to small in obesity (43)(44)(45)(46)(47)(48). This shift involved a lower prevalence of large-size HDL with apoE and a higher prevalence of small-size HDL with apoE in the obese group.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with previous studies, we found that the distribution of HDL sizes was significantly shifted from large to small in obesity (43)(44)(45)(46)(47)(48). This shift involved a lower prevalence of large-size HDL with apoE and a higher prevalence of small-size HDL with apoE in the obese group.…”
Section: Discussionsupporting
confidence: 82%
“…In this model, the cholesterol concentration in the fractions corresponding to VLDL (fractions 31-38), IDL (fractions 29 and 30), buoyant LDL (fractions [12][13][14], dense LDL (fractions 7-9), and HDL (fractions 1-5) was associated with IAF, whereas S I made no additional contribution to any of the fractions. In a third model, we included BMI as an independent variable together with IAF, S I , and SCF, and found that the cholesterol concentration in the fractions corresponding to VLDL (fractions [31][32][33][34][35][36][37][38], IDL (fraction 30), and dense LDL (fractions 8 -10) was associated with IAF, whereas S I again made no additional contribution. Thus IAF, but not S I , had independent effects to determine the cholesterol concentration beyond those of SCF and BMI.…”
Section: Dj Nieves and Associatesmentioning
confidence: 99%
“…Thus an increase in the waist-to-hip ratio (WHR) has been found to be associated with small dense LDL particles (26), as has been an increase in IAF mass (27,28) or insulin sensitivity (29,30). This pattern of central fat distribution has also been associated with an increase in VLDL and intermediate-density lipoprotein (IDL) (26,31) and a decrease in HDL 2 cholesterol (26,32,33). Although these analyses strongly suggest that central fat distribution and/or insulin resistance is an important determinant of adverse changes in lipoprotein profile, we believed that a critical examination of this issue in a large number of apparently healthy subjects was required to determine the impact of differences in body fat distribution and insulin sensitivity on plasma lipids.…”
mentioning
confidence: 99%
“…%BF was estimated by tetrapolar bioelectrical impedance (BIA-T, Quantum II, RJL System, MI, USA) according to Williams et al [16]. …”
Section: Methodsmentioning
confidence: 99%